Human Resources’ Burnout - Pirrolas, Olga Alexandra Chinita; Correia, Pedro Miguel Alves Ribeiro (Encyclopedia (Basel, Switzerland), 2024)
The reality of the occurrence of burnout in human resources has been increasingly recognised as a result of today’s transforming and competitive society, which exerts a very high level of stress and anxiety on workers, generating a notorious problem in the field of human resource management. Problems related to symptoms of exhaustion, mental weakness, personal devaluation, inability to solve professional problems, restlessness, and eating disorders. These problems manifest themselves in terms of personality, triggering feelings of threat, panic, nervousness, or suicide. Such disorders pose a threat not only to the person but also to the quality of their professional activities. In this way, burnout syndrome can cause a mental and physical breakdown requiring complex medical assistance. In view of the above, it is imperative that organisations take preventative and corrective measures to tackle this phenomenon. This entry covers topics such as the history of the concept of burnout, the concept, its causes and consequences, and predictive methods. By approaching the aforementioned topics using the existing literature on burnout syndrome, this entry aims to demystify the subject of burnout in human resources.